A review of the genus Hemidactylus Goldfuss, 1820 (Squamata: Gekkonidae) from Angola, with the description of two new species - Ceríaco, Luis M. P.; Agarwal, Ishan; Marques, Mariana P.; Bauer, Aaron M. (Zootaxa, 2020)
The genus Hemidactylus in Angola is represented by six species, all of them part of taxonomically and nomenclaturally challenging species complexes. We present a detailed taxonomic revision of the group in the region and describe two new species, Hemidactylus nzingae sp. nov. and Hemidactylus paivae sp. nov., both occuring in and potentially endemic to the highlands of Angola. Phylogenetic analysis using a combination of mitochondrial (ND2) and nuclear (MXRA5, PDC, RAG1) markers, as well as morphological and scalation data support the recognition of the new species. In addition, data support the revalidation of Hemidactylus bayonii Bocage, 1893, and Hemidactylus benguellensis Bocage, 1893. We also provide a redefinition of Hemidactylus longicephalus Bocage, 1873 with which we synonymize Hemidactylus mabouia molleri Bedriaga, 1892, from São Tomé in the Gulf of Guinea. Given that the type material of H. bayonii, H. benguellensis, H. longicephalus and H. mabouia molleri have all been lost or destroyed, we designate neotypes for all of these nomina for purposes of nomenclatural stability. The description of the new species and the revision and revalidation of the Angolan species already described contributes to a better understanding of the taxonomy and biogeography of West and Central African Hemidactylus, as well as to the general biogeographic and evolutionary patterns of Angolan fauna. A key to the Angolan species is also presented.